WILAYAH RAWAN LONGSOR DI KOTA JAYAPURA - Abrauw, Rudolf D (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2017)
Jayapura City is area that located in the north of the island of Papua and dealing directly with the Pacific Plate, so the potential for geological disasters, one of which is a landslide. However, landslides occur not only influenced by the movement of the Pacific Plate (because of occurrences fault / faults), but also a slope that varies from lowlands (0-8%) to the hills (> 45%), lithological and climatic conditions. This study aims to map areas vulnerable to landslides based Geographic Information System (GIS) using two models, namely, [1] the model prediction of landslides Directorate of Volcanology and Geological Hazard Mitigation (DVMBG) in 2005 with the parameters rainfall, geology, soil type, slope and land use; and [2] a combination of landslide prediction model of the Land Research Center with the parameters slope, rainfall, geology, soil type, distance of fault / faults and density of vegetation. The second result is verified with the data model of landslide occurrence during the period 2002-2014. The results showed that the application of the two models show the differences in the distribution of areas vulnerable to landslides. The first model produces an area prone to landslides with a high classification of 16780 hectares, while the second model recorded only 2184 Ha. Verification results with field data show that the second model is more representative and could be used to identify areas vulnerable to landslides in the city of Jayapura